Macroevolutionary dynamics of nectar spurs, a key evolutionary innovation. Issue 2 (23rd January 2019) - Fernández‐Mazuecos, Mario; Blanco‐Pastor, José Luis; Juan, Ana; Carnicero, Pau; Forrest, Alan; Alarcón, Marisa; Vargas, Pablo; Glover, Beverley J.
Summary: Floral nectar spurs are widely considered a key innovation promoting diversification in angiosperms by means of pollinator shifts. We investigated the macroevolutionary dynamics of nectar spurs in the tribe Antirrhineae (Plantaginaceae), which contains 29 genera and 300–400 species (70–80% spurred). The effect of nectar spurs on diversification was tested, with special focus on Linaria, the genus with the highest number of species. We generated the most comprehensive phylogeny of Antirrhineae to date and reconstructed the evolution of nectar spurs. Diversification rate heterogeneity was investigated using trait‐dependent and trait‐independent methods, and accounting for taxonomic uncertainty. The association between changes in spur length and speciation was examined within Linaria using model testing and ancestral state reconstructions. We inferred four independent acquisitions of nectar spurs. Diversification analyses revealed that nectar spurs are loosely associated with increased diversification rates. Detected rate shifts were delayed by 5–15 Myr with respect to the acquisition of the trait. Active evolution of spur length, fitting a speciational model, was inferred in Linaria, which is consistent with a scenario of pollinator shifts driving diversification. Nectar spurs played a role in diversification of the Antirrhineae, but diversification dynamics can only be fully explained by the complex interaction of multiple biotic and abiotic factors.